(untitled) (La U Investiga, 2018)
The main objective of the present investigation is to implement a guide on the technique of lactation for which a qualitative and quantitative, non-experimental, cross-sectional, descriptive type study was carried out with a population of 30 pregnant women In the Breastfeeding Process, a sample of 15 women belonging to the Health area of San Antonio de Ibarra was taken in a period of 4 months (October 2016 to February 2017); Those who attended the prenatal check-ups and the care of the healthy child at the San Antonio Health Center, where they studied the level of knowledge, techniques on breastfeeding and the correct positions to breastfeed the child and others during Feeding the baby; For which a survey was made up of 10 items, including open and closed questions. After analyzing the data obtained it is determined that there is a direct relationship between the level of schooling and the level of knowledge, obtaining the following results that 66.67% of mothers have a knowledge about the techniques, while a 33, 33% Dice have insufficient knowledge of the subject in question. The other result indicates that 100% of the sample is in agreement in the execution of the guide. Finally, the successful acceptance of the guide was verified through an unbiased presentation given to the beneficiaries of the present project.